(untitled) (Journal of Face Aesthetics, 2023)
Facial aesthetic medicine is a young component of aesthetic medicine that raises a lively polemic on a number of issues on both medical and ethical grounds. The main focus of (non‑therapeutic) aesthetics turns to the improvement and correction of the face and neck to get from what is good to an even better, more beautiful, aesthetically pleasing, younger face. However, when qualifying a patient for aesthetic treatments, it is important to approach the issue holistically, to pay attention to all aspects: psychological state, social and cultural conditions and a holistic attitude towards life. Any worrying symptoms should not be underestimated. Thus, the practitioner of aesthetic medicine should always bear in mind two very topical truths of ancient origin: primum non nocere and salus aegroti suprema lex.